Empire's mistress, starring Isabel Rosario Cooper - Gonzalez, Vernadette Vicuña 1973- (Durham Duke University Press, 2021)
"Empire's Mistress centers the life of Isabel Rosario Cooper, a mixed race vaudeville and film actor from the Philippines, notorious for being Douglas MacArthur's one-time mistress. Tracking her story through absences and traces in the archive, Gonzalez explores empire on the scale of the intimate. Cooper's itinerant life-from Manila, to Washington, D.C. and Los Angeles-is a rich text for understanding the mobilities and opportunities available to women like her in the first half of the twentieth century. Empire's Mistress wrests the story of Isabel Cooper away from the plot of the tragic Eurasian, while attending to the haunting legacies of race, sex, and empire that define her life, both onstage/onscreen, and off"
This Is Not a Love Story -- Death Certificate, Partial -- A General and Unruly Wards -- The Flower of Cathay, Excerpts -- Misapprehensions -- The Farm Boy and the Unbiddable Wife -- The Delicate Moonbeam -- "Dimples" : Innocence (Colonial Kink) -- Stage Presence -- Letters Lost at Sea, Imagined, Excerpts -- The New Filipina, Kissing -- Gossip : Fiction and Nonfiction -- "It Girl" Meets General -- Recipe for the Douglas -- The Washington Housewife, the Hollywood Hula Girl, and the Two Husbands : Reinventions -- Out of Place -- 1st Filipina Nurse, Geisha, Little Sergeant, Javanese Nurse, Uncredited -- Lolita's Lines -- Bit Parts : Racial Types, Ensemble -- Caged Birds -- For Future Archives, Apocrypha, and Fictions -- Death Certificate, Entire -- The Suicide -- Last Review.
Includes bibliographical references and index
Keywords: Cooper, Isabel Rosario -- 1914-1960.; MacArthur, Douglas -- 1880-1964 -- Relations with women; Motion picture actors and actresses -- Philippines -- Manila -- Biography; Filipino American women -- Biography